A tool for community-based assessment of the implications of development on water security in hillside watersheds - Luijten, JC; Jones, James W.; Knapp, E.B. (Elsevier, 2001)
Development and population growth in Latin American countries with steep slope farming are likely to further increase pressures on water and land resources. A methodology was developed for assessing water availability and use under different development pathways at a watershed scale to determine whether water security is a potential problem, and if so, under what conditions it is likely to occur. This methodology makes use of a GIS-based spatial water budget model for simulating stream water availability, water use and stream flow control on a daily basis at a watershed scale. Here, we analysed water availability under three plausible development scenarios for the 3246 ha Cabuyal River watershed in southwest Colombia in the year 2025: Corporate Farming (CF), Ecological Watershed (EW), and Business as Usual (BU). Simulated average river flows at the watershed outlet were, respectively, 874, 796 and 925 l s?1 for the CF, EW and BU scenarios. The contribution of base flow to river flow (base flow index) was on average, 80.8, 85.6 and 77.9%, respectively, for the three scenarios. The watershed had the potential to meet the anticipated increase in water use under each explorative scenario. However, dams were necessary to store irrigation water in the CF scenario, otherwise over 60% of the available water would have been used during the dry season. Such a high figure raises concerns about effects on aquatic and riparian ecology, concentrations of potential contaminants, water reserves for especially low rainfall years, and the watershed resilience to meet temporarily higher water needs during the day. Analyses indicated that current water-use conflicts in the watershed can be resolved if irrigation water supply is separated from drinking water supply. This study helped reduce some of the complexity associated with the interdependencies between land and water resources, the impact of using them, and spatial linkages within the watershed. Results of this study can be used for teaching local stakeholders about basic landscape responses and helping multi-institutional alliances to become proactive and to guide development to the benefit of local communities.